2020
DOI: 10.1109/access.2019.2961295
|View full text |Cite
|
Sign up to set email alerts
|

Interval Estimation of Landslide Displacement Prediction Based on Time Series Decomposition and Long Short-Term Memory Network

Abstract: Interval estimation of landslide displacement prediction is significant for landslide early warning. The goal of this paper is to improve the accuracy of landslide displacement point prediction and quantify the uncertainties associated with the predicted values. To do so, a coupling prediction model based on double moving average (DMA) method and long short-term memory (LSTM) network is investigated. The DMA method is employed to decompose cumulative displacement of landslide into trend and periodic displaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Taking the Baishuihe landslide located in the Three Gorges Reservoir area as a case study, the proposed model showed satisfactory performance. Another study [29] investigated a coupling prediction model based on the double moving average (DMA) method and the LSTM network to improve the accuracy of landslide displacement point prediction and quantify the uncertainties associated with the predicted values.…”
Section: Related Workmentioning
confidence: 99%
“…Taking the Baishuihe landslide located in the Three Gorges Reservoir area as a case study, the proposed model showed satisfactory performance. Another study [29] investigated a coupling prediction model based on the double moving average (DMA) method and the LSTM network to improve the accuracy of landslide displacement point prediction and quantify the uncertainties associated with the predicted values.…”
Section: Related Workmentioning
confidence: 99%
“…With the improvement of computer calculating ability and the development of machine learning and artificial intelligence, the disaster-prediction ability of landslides has been greatly improved. At present, the commonly used models for landslide displacement prediction include the backpropagation neural network (BPNN) [14,15,23], support-vector regression (SVR) [18,[24][25][26][27][28], extreme learning machine (ELM) [29][30][31][32], kernel extreme learning machine (KELM) [14,23,33], long short-term memory (LSTM) [25,[34][35][36][37], decision tree [38], and so on. Moreover, many algorithms are used to optimize the parameters of the prediction models, including the genetic algorithm (GA) [28,39,40], particle swarm optimization (PSO) [16,26,28,29,41,42], fruit fly optimization algorithm (FOA) [18], grey wolf optimizer (GWO) [15], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2018) proposed using a bootstrapbased ELM to construct PIs for landslide incremental displacement. Xing et al (2019) revised the structure of long short-term memory (LSTM) network to generate probabilistic forecasting of landslide displacement and produced highquality PIs for future displacement. Jiang et al (2021) proposed a hybrid grey wolf optimizer to optimize the ELM structure for PI construction and achieved improved probabilistic prediction performance using field data.…”
Section: Introductionmentioning
confidence: 99%